Marketing strategies to improve the sales of bakery products of small-medium enterprise (SMEs) in Malaysia - Kiumarsi, Seraj; Jayaraman, Krishnaswamy; Mohd Isa, Salmi; Varastegani, Asra (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
Bakery products become a regular food in most part of the world and are essential commodities today. There is a high potential for business growth in selling bakery products. In the business world, Small-Medium Enterprises (SMEs) are primarily engaged in the bakery business, but cannot compete with the branded bakery Industry. The SMEs in Malaysia are striving hard to achieve growth in the business of bakery products. The present case study deals with the issues faced by SMEs and provided some valid recommendations to resolve the existing problems in the bakery business. The case analysis and its findings reveal that SMEs have unstructured marketing strategies and needs enhancements in the areas of packaging, value add to the bakery products, focus on promotion and appropriate advertising strategies. Further, the analysis reveals that more coverage of selling points for bakery products, the increased number of distribution centers and proper incentives to the agents may definitely improve the marketing of bakery products.